Female Enr emale Enrolments in STEM in Higher E olments in STEM in Higher Education: T ducation: Trend Analysis end Analysis from 2003 – 2018: KNUST as a case study - Lamptey, Richard Bruce; Titiloye, Kemi; Adoma Pels , Welhemina (University of Nebraska - Lincoln, 2024)
This article is published by University of Nebraska - Lincoln, 2020 and is also available at https://digitalcommons.unl.edu/libphilprac/4327